Equipment qualification in testing the flexural resistance of bended ceramic tiles - Pavlović Ana; Ubertini Francesco (FME Transactions, 2016)
The capability to bend in a controlled manner Grès Porcelain stoneware tiles passing by a processes of pyroplastic deformation opens up new opportunities in utilisation of this important family of ceramics. A bent tile can be used in innovative applications, such as stairs, shelves, benches and even radiators, turning this element from a simple piece of furnishing in a modern functional component. But this change in functionality requires a new and different approach to the quality control that can no longer be limited to the validation tests as specified in the regulations used for traditional ceramics (e.g. colour, porosity, hygroscopic ...). Starting from a brief description of the first and only device devised for the verification of flexural resistance of curved tiles, this paper investigates the limitations and possibilities of use of that innovative equipment for product/process quality monitoring. Thanks to a careful modelling of its mechanism of operation, accompanied by various simulations comparing the limit cases of use, it has been possible to verify the incidence of some of the potential weaknesses of the equipment as well as to carry out a sensitivity analysis of this new tool for measure.